ISSUES AND GAPS IN EMOTIONAL INTELLIGENCE STUDIES - Sopian, Bujang; Nadri Aetis Heromi, Basmawi; Hasriq, Hadil (Publications International Lahore, Pakistan, 2023)
Emotional intelligence study is vital in the working environment to determine employee competency. However, understanding the issues and gaps are the biggest challenge for organization and researcher. This paper will uncover the Issues and gaps in emotional intelligence profiling for competency profiling in an international context. Three (3) Gaps will be addressed in this paper, namely: The empirical gap, followed by the theoretical gap and the practical gap. From the issues and gaps, further research and concept can be developed to solve today's issues related to emotional intelligence and competency.